Regulation, Location and Activity of Plasminogen Activator Inhibitor 2 (PAI-2) in Peripheral Blood Monocytes, Macrophages and Foam Cells - Ritchie, Helen; Jamieson, Alec; Booth, Nuala A (Thrombosis and Haemostasis, 1997)
Monocytes, macrophages and foam cells are central to atherogenesis. We have examined the potential ability of monocytes, macrophages and foam cells to affect the stability of deposited fibrin, characteristic of the atherosclerotic plaque, by their production of plasminogen activators and their inhibitors. Monocytes respond to thrombin and LPS by up-regulation of PAI-2 synthesis, and PAI-2 is their major product among the plasminogen activators/inhibitors. In contrast, macrophages and foam cells, while they did produce PAI-2, did not respond to thrombin and LPS by an increase in its synthesis. All PAI-2 produced by macrophages and foam cells was accumulated intracellularly, whereas monocytes also secreted PAI-2. Secreted PAI-2 was active as an inhibitor of u-PA, whereas intracellular PAI-2 required detergent treatment to generate activity. Thus monocytes, but not macrophages or foam cells, produce and secrete active PAI-2, thus potentially affecting fibrin stability in the local environment.